Surface-coated inorganic particles, their method of manufacture, and organic solvent dispersions containing the particles

Coating inorganic particles with a silicate compound and an α,β-unsaturated carbonyl group reaction product enhances dispersibility and optical properties, addressing the limitations of existing technologies.

JP7617446B2Active Publication Date: 2025-01-20ISHIHARA SANGYO KAISHA LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022507168
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-10
Filing Date
2021-03-08
Publication Date
2025-01-20
Estimated Expiration
2041-03-08

AI Technical Summary

Technical Problem

Existing surface-coated inorganic particles do not achieve sufficient dispersibility in organic solvents, and their coatings lack improved transparency and refractive properties.

Method used

Coating inorganic particles with a reaction product of a silicate compound having an amino group and/or its hydrolysis product and a compound having one α,β-unsaturated carbonyl group, such as ethylene glycol chains or methacrylates, to enhance dispersibility and optical properties.

Benefits of technology

The resulting surface-coated inorganic particles exhibit improved dispersibility in organic solvents, leading to better transparency and refractive properties in organic solvent dispersions and coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617446000001
    Figure 0007617446000001
  • Figure 0007617446000002
    Figure 0007617446000002
  • Figure 0007617446000003
    Figure 0007617446000003
Patent Text Reader

Abstract

Provided are: surface-coated inorganic particles which can have improved dispersibility in organic solvents and enable the function and performance of the original inorganic particles to be sufficiently exhibited; and a method for producing the surface-coated inorganic particles. Also provided are an organic-solvent dispersion and a coating film which are excellent in terms of transparency and refraction property. The surfaces of inorganic particles, e.g., titanium oxide, are coated with a product of reaction between an aminated silicate compound, e.g., aminopropyltrimethoxysilane, and / or a product of the hydrolysis thereof and a compound having one α,β-unsaturated carbonyl group in the molecule, e.g., an alkoxypolyalkylene glycol (meth)acrylate.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to surface-coated inorganic particles and a method for producing the same, an organic solvent dispersion in which the same is dispersed and a method for producing the same, and further to a coating composition containing the same and a method for producing a surface-coated inorganic particle layer. [Background technology]

[0002] Various inorganic particles such as metal oxides, metal nitrides, and metals are used for various purposes such as pigments, ultraviolet shielding agents, infrared shielding agents, visible light transmittance agents, fillers, hard coat agents, and refractive index adjusters. In this case, they may be surface-coated with an organic compound in order to improve dispersibility in a dispersion medium and improve functions such as shielding and transparency. For example, Patent Document 1 discloses metal oxide core particles having a coating layer containing an inorganic substance, (i) a quaternary silane coupling agent and / or (ii) a silane coupling agent, and a hydrophobizing agent, and describes that an aminosilane coupling agent is specifically used as the silane coupling agent to exhibit effective UV absorption properties, reduced photoactivity, and improved skin feel. Patent Document 2 discloses a method for producing polymerizable particles, which comprises reacting an aminosilane compound (a) containing a primary or secondary amino group and an alkoxysilyl group with a compound (b) having at least two unsaturated double bonds to produce a compound (c) having an alkoxysilyl group and an unsaturated double bond, with metal oxide particles (d) having on their surfaces functional groups capable of reacting with alkoxysilyl groups. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Special Publication No. 2015-531734 [Patent Document 2] JP 2005-220243 A Summary of the Invention [Problem to be solved by the invention]

[0004] In the above-mentioned Patent Document 1, by having a coating layer containing an aminosilane coupling agent, the dispersibility of the surface-coated particles in a dispersion medium is improved compared to the level at that time, but at present, further improvement is required. In addition, when the organic-inorganic composite particles described in Patent Document 2 are used in a coating agent, a cured coating film having better transparency, scratch resistance, hardness, solvent resistance, and adhesion than the level at that time can be produced, but at present, there is a demand for the development of new surface-coated particles that can provide organic solvent dispersions and coating films with further improved transparency and refraction properties. [Means for solving the problem]

[0005] The present inventors conducted extensive research in order to improve the dispersibility of inorganic particles coated with an organic compound in organic solvents, and discovered that desired dispersibility in organic solvents can be obtained by coating the surfaces of inorganic particles with a product obtained by reacting a silicate compound having an amino group with a compound having one α,β-unsaturated carbonyl group in the molecule, and that the obtained organic solvent dispersions and coating films of the surface-coated inorganic particles can be made to have excellent transparency and refractive index, thereby completing the present invention.

[0006] That is, the present invention provides (1) Surface-coated inorganic particles, the surface of which is coated with a reaction product of a silicate compound having an amino group and / or its hydrolysis product with a compound having one α,β-unsaturated carbonyl group in the molecule; (2) The surface-coated inorganic particles according to (1), wherein the compound having an α,β-unsaturated carbonyl group is a compound further having an ether bond. (3) The surface-coated inorganic particles according to (1) or (2), wherein the compound having an α,β-unsaturated carbonyl group is a compound having an ethylene glycol chain (polymerization number n=2 to 10), a propylene glycol chain (polymerization number n=2 to 10), or a 5- or 6-membered cyclic group. (4) The surface-coated inorganic particles according to any one of (1) to (3), wherein the compound having an α,β-unsaturated carbonyl group is a (meth)acrylate having a 5- to 6-membered cyclic group or an alkoxy polyalkylene glycol (meth)acrylate. (5) The surface-coated inorganic particles according to any one of (1) to (4), wherein the compound having an α,β-unsaturated carbonyl group is tetrahydrofurfuryl acrylate, methoxytriethylene glycol acrylate, methoxypolyethylene glycol acrylate, or methoxydipropylene glycol acrylate. (6) Surface-coated inorganic particles according to any one of (1) to (5), in which, when the amount of the amino group in the silicate compound having an amino group and / or the hydrolysis product thereof in the reaction product is a mole and the amount of the compound having an α,β-unsaturated carbonyl group is b mole, the ratio of a / b is 0.8≦a / b≦10. (7) The surface-coated inorganic particles according to any one of (1) to (6), wherein the reaction product is a low molecular weight silicate compound having 3 to 100 carbon atoms and / or a hydrolysis product thereof. (8) The surface-coated inorganic particles according to any one of (1) to (7), wherein the inorganic particles are composed of an inorganic core particle and an inorganic compound coated on the surface of the inorganic core particle. (9) Surface-coated inorganic particles, in which the inorganic particle according to any one of (1) to (7) or the inorganic core particle according to (8) is a titanium oxide particle. (10) An organic solvent dispersion of surface-coated inorganic particles, in which the surface-coated inorganic particles according to any one of (1) to (9) are dispersed in an organic solvent. (11) A coating composition comprising the surface-coated inorganic particles according to any one of (1) to (9), an organic solvent, and a resin. (12) A coating composition comprising the organic solvent dispersion according to (10) and a resin. (13) a first step of mixing inorganic particles with a silicate compound having an amino group and / or a hydrolysis product thereof in an aqueous solvent to coat the surfaces of the inorganic particles with the silicate compound having an amino group and / or a hydrolysis product thereof; Next, a second step of replacing the aqueous solvent with an organic solvent, and then mixing a compound having one α,β-unsaturated carbonyl group in the molecule to coat the surfaces of the inorganic particles with a reaction product of the silicate compound having an amino group and / or its hydrolysis product and the compound having an α,β-unsaturated carbonyl group; A method for producing surface-coated inorganic particles, (14) The method for producing surface-coated inorganic particles according to (13), wherein in the second step, a surfactant and an organic solvent are mixed with an aqueous solvent to transfer the inorganic particles to the organic solvent, and then the aqueous solvent is replaced with an organic solvent, and the compound having an α,β-unsaturated carbonyl group is mixed therewith. (15) A method for producing surface-coated inorganic particles, which comprises mixing inorganic particles with a silicate compound having an amino group and / or a hydrolysis product thereof, and a compound having one α,β-unsaturated carbonyl group in the molecule, and coating the surfaces of the inorganic particles with a reaction product of the silicate compound having an amino group and / or a hydrolysis product thereof and the compound having an α,β-unsaturated carbonyl group; (16) The method for producing surface-coated inorganic particles according to any one of (13) to (15), wherein a moles of the amino group in the silicate compound having an amino group and / or its hydrolysis product and b moles of the compound having an α,β-unsaturated carbonyl group satisfy 0.8≦a / b≦10. (17) A third step of adding a poor solvent to the organic solvent dispersion obtained in the second step according to (13) or (14) to perform solid-liquid separation to recover surface-coated inorganic particles; Then, a fourth step of dispersing the recovered surface-coated inorganic particles in an organic solvent; A method for producing an organic solvent dispersion of surface-coated inorganic particles, comprising: (18) A method for producing an organic solvent dispersion of surface-coated inorganic particles, which comprises mixing inorganic particles, an amino group-containing silicate compound and / or its hydrolysis product, and a compound having one α,β-unsaturated carbonyl group in the molecule in an organic solvent, coating the surfaces of the inorganic particles with a reaction product of the amino group-containing silicate compound and / or its hydrolysis product, and the compound having an α,β-unsaturated carbonyl group, and dispersing the reaction product in the organic solvent. (19) The method for producing the organic solvent dispersion according to (18), wherein a moles of the amino group in the silicate compound having an amino group and / or its hydrolysis product and b moles of the compound having an α,β-unsaturated carbonyl group satisfy 0.8≦a / b≦10. (20) A method for producing a surface-coated inorganic particle layer, which comprises applying or spraying an organic solvent dispersion of the surface-coated inorganic particles according to (10) or a coating composition according to (11) or (12) onto a substrate. And so on. Effect of the Invention

[0007] According to the present invention, the dispersibility of inorganic particles in an organic solvent can be sufficiently improved, and the inorganic particles can thus fully exhibit their functions and performance. Furthermore, the organic solvent dispersions and coating films of the surface-coated inorganic particles obtained according to the present invention can provide transparency and refractive index superior to those of conventional organic solvent dispersions and coating films of surface-coated inorganic particles. Moreover, the surface-coated inorganic particles of the present invention and their organic solvent dispersions can be produced by a simple method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present invention relates to surface-coated inorganic particles, the surfaces of which are coated with a reaction product of a silicate compound having an amino group and / or its hydrolysis product and a compound having one α,β-unsaturated carbonyl group in the molecule.

[0009] The inorganic particles are not particularly limited, but examples thereof include metal oxide particles such as zinc oxide, titanium oxide, zirconium oxide, tin oxide, cerium oxide, iron oxide, and silicon oxide, metal composite oxide particles such as barium titanate, strontium titanate, and calcium titanate, metal nitrides such as titanium nitride, titanium oxynitride, silicon nitride, silicon oxynitride, aluminum nitride, and aluminum oxynitride, metal compound particles such as metal carbides such as titanium carbide, zirconium carbide, silicon carbide, and aluminum carbide, and metal particles such as metal copper, silver, and gold. The average particle size of the inorganic particles can be appropriately designed according to the application, and is preferably in the range of 1 nm to 50 μm (i.e., 1 nm or more and 50 μm or less), more preferably 2 nm to 5 μm (i.e., 2 nm or more and 5 μm or less), even more preferably 3 nm to 500 nm (i.e., 3 nm or more and 500 nm or less), and most preferably 3 nm to 100 nm (i.e., 3 nm or more and 100 nm or less). The average particle size is a value obtained by measuring the longest straight line portions of 100 particles in an electron micrograph of the inorganic particles and averaging these measured values.

[0010] The inorganic particles may be composed of inorganic particles themselves, or may be composed of inorganic core particles and an inorganic compound coated on the surface thereof. Examples of inorganic core particles include the above-mentioned inorganic particles such as titanium oxide, zinc oxide, silicon oxide, and aluminum oxide, and the particle surface is preferably coated with an inorganic compound such as an oxide or hydroxide of silicon, aluminum, tin, zinc, titanium, antimony, zirconium, etc. When the inorganic particles are composed of inorganic particles themselves, the inorganic particles are preferably titanium oxide particles. When the inorganic particles are composed of inorganic core particles and an inorganic compound coated on the surface thereof, the inorganic core particles are preferably titanium oxide particles. Coating with an inorganic compound refers to a state in which the inorganic compound is adsorbed or precipitated on the surface of the inorganic core particles, and the inorganic compound is present on the surface of the inorganic core particles. Coating with an inorganic compound may be a state in which the inorganic compound is present on at least a part of the surface of the inorganic particles. The amount of the inorganic compound coated is preferably 0.1 to 50 parts by mass (i.e., 0.1 to 50 parts by mass) relative to 100 parts by mass of the inorganic particles, more preferably 0.5 to 40 parts by mass (i.e., 0.5 to 40 parts by mass), and even more preferably 1 to 30 parts by mass (i.e., 1 to 30 parts by mass). The surface of the inorganic core particle of titanium oxide is preferably coated with an inorganic compound such as an oxide or hydroxide of silicon, aluminum, tin, zinc, titanium, antimony, zirconium, etc., and can be used as a titanium dioxide pigment, titanium dioxide fine particles, etc. When used as a titanium dioxide pigment, the average particle size is preferably 0.1 μm to 0.5 μm (i.e., 0.1 to 0.5 μm), more preferably 0.15 μm to 0.4 μm (i.e., 0.15 to 0.4 μm), and even more preferably 0.2 to 0.3 μm (0.2 to 0.3 μm). When used as titanium oxide fine particles, the average particle size is preferably 1 nm to 100 nm (ie, 1 nm or more and 100 nm or less), more preferably 2 nm to 80 nm (ie, 2 nm or more and 80 nm or less), and even more preferably 3 nm to 50 nm (ie, 3 nm or more and 50 nm or less).

[0011] The reactant coated on the surface of the inorganic particles is obtained by the reaction of a silicate compound having an amino group and / or its hydrolysis product with a compound having one α,β-unsaturated carbonyl group in the molecule. Such a reaction is called a Michael addition reaction, which is a reaction in which a silicate compound having an amino group is added to a mono-α,β-unsaturated carbonyl compound having one C=C bond in the molecule (i.e., a compound having one α,β-unsaturated carbonyl group in the molecule). For this reason, the reactant is sometimes called a Michael adduct. The reactant is understood to be a compound in which a silicate compound and / or its hydrolysis product is added to a compound having one α,β-unsaturated carbonyl group in the molecule via an amino group. The Michael addition reaction is preferably carried out in the presence of inorganic particles, and the resulting Michael adduct can be coated on the surface of the inorganic particles. The Michael addition reaction may be a reaction in which no hydrogen of the amino group remains among the amino groups (NH2) of the silicate compound and / or its hydrolysis product, that is, a reaction in which two hydrogen of the amino group are added to two moles of the compound having an α,β-unsaturated carbonyl group and no hydrogen of the amino group remains, but a reaction in which one hydrogen of the amino group (NH) remains is preferred, that is, a reaction in which one hydrogen of the amino group is added to one mole of the compound having an α,β-unsaturated carbonyl group and one hydrogen of the amino group remains. For this reason, when the amino group of the silicate compound having an amino group and / or its hydrolysis product is a mole and the compound having one α,β-unsaturated carbonyl group in the molecule is b mole, the reaction is preferably carried out at a molar ratio of 0.8≦a / b≦10, more preferably 1≦a / b≦10, even more preferably 1≦a / b≦8, and most preferably 1≦a / b≦6.

[0012] Specific examples of silicate compounds having an amino group include -C-Si(OH)3 silanol compounds, -C-Si(OR)3 alkoxysilane compounds, -C-Si(OR) x R´ 3-x (wherein x is an integer of 1 to 3 (that is, 1 or more and 3 or less)), and more preferably contains a hydrolyzable group such as an alkoxy group represented by the following general formula (1).

[0013] [ka]

[0014] In the above general formula (1), x represents an integer of 1 to 3 (i.e., 1 to 3), y represents an integer of 0 to 2 (i.e., 0 to 2), and z represents an integer of 0 to 1 (i.e., 0 or 1), where x+y+z=3. 1 , R 2 and R 3 each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms (that is, 1 or more and 4 or less).

[0015] Specific examples of silicate compounds having an amino group include amino group-containing alkoxysilanes and amino group-containing di(alkoxysilanes). Examples of the former include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, 3-(trimethoxysilylpropyl)aminopropyltrimethoxysilane, 3-(triethoxysilylpropyl)aminopropyltriethoxysilane, 2-(trimethoxysilylpropyl)aminoethyl-3-aminopropyltrimethoxysilane, and 2-(triethoxysilylpropyl)aminoethyl-3-aminopropyltriethoxysilane. The latter includes, for example, bis(trimethoxysilylpropyl)amine, and the hydrolysis products thereof can be prepared and used.

[0016] The compound having one α,β-unsaturated carbonyl group in the molecule is not particularly limited as long as it is a mono-α,β-unsaturated carbonyl compound having one C=C bond in the molecule, and is preferably one having a skeleton represented by the following general formula (2). In addition, the compound having one α,β-unsaturated carbonyl group in the molecule is more preferably a compound further having an ether bond in the molecule, and as the compound having an ether bond, an ethylene glycol chain having a polymerization number n=2 to 10 (i.e., 2 to 10), a propylene glycol chain having a polymerization number n=2 to 10 (i.e., 2 to 10), or a compound having a 5- to 6-membered cyclic group (i.e., a 5- or 6-membered cyclic group) is more preferable, and (meth)acrylates or alkoxy polyalkylene glycol (meth)acrylates having a 5- to 6-membered cyclic group are even more preferable. The term "(meth)acrylate" means acrylate and / or methacrylate (sometimes referred to as methacrylate).

[0017] [ka]

[0018] In the above general formula (2), R 4 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms (that is, 1 or more and 4 or less).

[0019] Specific examples of the compound having one α,β-unsaturated carbonyl group in the molecule include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, stearyl (meth)acrylate, and lauryl (meth)acrylate; cyclohexyl (meth)acrylate. (Meth)acrylates having 5-6 membered cyclic groups, such as tetrahydrofurfuryl (meth)acrylate, isobornyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, and phenoxypolyethylene glycol (meth)acrylate; methoxydiethylene glycol (meth)acrylate, methoxytriethylene glycol (meth)acrylate, and methoxypolyethylene glycol (meth)acrylate, alkoxy polyalkylene glycol (meth)acrylates such as methoxy dipropylene glycol (meth)acrylate, methoxy polypropylene glycol (meth)acrylate, and ethoxy polyethylene glycol (meth)acrylate; hydroxyl group-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, glycerol (meth)acrylate, polyethylene glycol (meth)acrylate, and polypropylene glycol (meth)acrylate; N-substituted (meth)acrylamides such as (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, diacetone (meth)acrylamide, and acryloylmorpholine; and amino group-containing (meth)acrylates such as N,N-dimethylaminoethyl (meth)acrylate and N,N-diethylaminoethyl (meth)acrylate.In addition to the above-mentioned compounds, further examples include polyester (meth)acrylate, polyurethane (meth)acrylate, epoxy (meth)acrylate, (meth)acrylated maleic acid modified polybutadiene, and the like. Among these, (meth)acrylates or alkoxypolyalkylene glycol (meth)acrylates having a 5- to 6-membered cyclic group are preferred, with tetrahydrofurfuryl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate or methoxydipropylene glycol (meth)acrylate being more preferred, and among the more preferred ones, the acrylates tetrahydrofurfuryl acrylate (hereinafter sometimes referred to as "THF-A"), methoxytriethylene glycol acrylate (hereinafter sometimes referred to as "methoxy-triethylene glycol acrylate" or "MTG-A"), methoxypolyethylene glycol acrylate (hereinafter sometimes referred to as "130A") or methoxydipropylene glycol acrylate (hereinafter sometimes referred to as "methoxydipropylene glycol acrylate" or "DPM-A") are the most preferred.

[0020] The term "the reactant is coated on the surface of the inorganic particle" means that the reactant is adsorbed, precipitated or reacted on the surface of the inorganic particle, and the reactant or a part of the reactant is present in a modified state (for example, the alkoxy group is decomposed and separated into an alkyl group and a hydroxyl group, and the reactant is adsorbed to the inorganic particle by the hydroxyl group (-Si-OH-), or the reactant is present on the surface of the inorganic particle in a hydrolyzed state). The reactant is preferably a low molecular silicate compound having 3 to 100 carbon atoms (i.e., 3 to 100), and / or a hydrolysis product thereof, more preferably a low molecular silicate compound having 3 to 50 carbon atoms (i.e., 3 to 50), and even more preferably a low molecular silicate compound having 3 to 40 carbon atoms (i.e., 3 to 40).

[0021] The coating of the reaction product may be present on at least a part of the surface of the inorganic particles, and in order to disperse the inorganic particles sufficiently in an organic solvent, it is preferable to coat the inorganic particles as densely as possible. The coating amount is preferably 0.1 to 50 parts by mass (i.e., 0.1 to 40 parts by mass), more preferably 0.5 to 40 parts by mass (i.e., 0.5 to 40 parts by mass), and even more preferably 1 to 30 parts by mass (i.e., 1 to 30 parts by mass) relative to 100 parts by mass of the inorganic particles.

[0022] Next, a dispersion in which the above-mentioned surface-coated inorganic particles are dispersed in an organic solvent will be described. In the present application, the dispersion in which the above-mentioned surface-coated inorganic particles are dispersed in an organic solvent will be referred to as an organic solvent dispersion, and the organic solvent can be appropriately selected. Specifically, hydrocarbon solvents such as toluene, xylene, solvent naphtha, normal hexane, isohexane, cyclohexane, methylcyclohexane, normal heptane, tridecane, tetradecane, and pentadecane; methanol, EtOH (ethanol), butanol, IPA (isopropyl alcohol), normal propyl alcohol, 2-butanol, TBA (tertiary butanol), etc. alcohol-based solvents such as acetone, MEK (methyl ethyl ketone), methyl isobutyl ketone, DIBK (diisobutyl ketone), cyclohexanone, DAA (diacetone alcohol); ketone-based solvents such as ethyl acetate, butyl acetate, methoxybutyl acetate, cellosolve acetate, amyl acetate, normal propyl acetate, isopropyl acetate, methyl lactate, ethyl lactate, butyl lactate, γ-butyl lactone; methyl cellosolve, cellosolve, At least one selected from the following can be used: ether solvents such as butyl cellosolve, dioxane, MTBE (methyl tertiary butyl ether), and butyl carbitol; glycol solvents such as ethylene glycol, diethylene glycol, triethylene glycol, and propylene glycol; glycol ether solvents such as diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, PGME (1-methoxy-2-propanol, i.e., propylene glycol monomethyl ether), and 3-methoxy-3-methyl-1-butanol; glycol ester solvents such as ethylene glycol monomethyl ether acetate, PGMEA (propylene glycol monomethyl ether acetate), diethylene glycol monobutyl ether acetate, and diethylene glycol monoethyl ether acetate; and amide solvents such as DMF (N,N-dimethylformamide), DEF (N,N-diethylformamide), DMAc (N,N-dimethylacetamide), and NMP (N-methylpyrrolidone).Among these solvents, it is preferable to use an alcohol-based solvent or a glycol ether-based solvent, and it is more preferable to use methanol, ethanol, butanol, IPA (isopropyl alcohol) or PGME (1-methoxy-2-propanol, i.e., propylene glycol monomethyl ether). The content of the surface-coated inorganic particles is preferably 0.1 to 95 parts by mass (i.e., 0.1 to 95 parts by mass), more preferably 10 to 90 parts by mass (i.e., 10 to 90 parts by mass), and even more preferably 15 to 90 parts by mass (i.e., 15 to 90 parts by mass) relative to 100 parts by mass of the organic solvent.

[0023] Next, a coating composition containing the surface-coated inorganic particles, an organic solvent, and a resin, or a coating composition containing the organic solvent dispersion and a resin will be described. The organic solvents described above can be used. Any resin can be used as the resin, and for example, a dissolution type in a low polarity non-aqueous solvent, an emulsion type, a colloidal dispersion type, etc. can be used without limitation. In addition, examples of resin types include various modified polyester resins such as polyester resin, urethane-modified polyester resin, epoxy-modified polyester resin, and acrylic-modified polyester, polyether urethane resin, polycarbonate urethane resin, vinyl chloride-vinyl acetate copolymer, epoxy resin, phenolic resin, acrylic resin, polyamideimide, polyimide, modified celluloses such as ethyl cellulose, hydroxyethyl cellulose, nitrocellulose, cellulose-acetate-butyrate (CAB), and cellulose-acetate-propionate (CAP); polyethylene glycol; and polyethylene oxide. The amount of the resin is preferably in the range of about 0.5 to 100 parts by mass, more preferably about 1 to 50 parts by mass, and even more preferably about 2 to 25 parts by mass, per 100 parts by weight of the surface-coated inorganic particles.

[0024] Specific examples of resins include the Aronix (registered trademark) series B-309, B-310, M-430, M-406, M-460, and M-1100 (manufactured by Toagosei Co., Ltd.); the Light Acrylate (registered trademark) series MTG-A, DPM-A, THF-A, IB-XA, HOA-HH(N), 1,6HX-A, 1,9ND-A, PE-3A, and PE-4A (manufactured by Kyoeisha Chemical Co., Ltd.); the Epolite (trade name) series 40E, 4000, and 3002(N) (manufactured by Kyoeisha Chemical Co., Ltd.); the NK Ester (registered trademark) series A-TMM-3, A-9550, and A-DPH (manufactured by Shin-Nakamura Chemical Co., Ltd.); and the KAYARAD (registered trademark) series DPHA, DPEA-12, and DPCA-60 (manufactured by Nippon Kayaku Co., Ltd.).

[0025] The organic solvent dispersion or coating composition can be applied or sprayed onto a substrate to form a layer of surface-coated inorganic particles, and cured as necessary. When titanium oxide fine particles are used as the surface-coated inorganic particles, a titanium oxide layer having high hardness and high visible light transmittance can be formed, and can be used as a hard coat, a high refractive index layer, or an ultraviolet shielding layer. The substrate is not particularly limited, and glass, plastic, ceramic, metal, etc. can be used. The film thickness can be appropriately set.

[0026] The surface-coated inorganic particles can be prepared by mixing a reaction product of a silicate compound having an amino group and / or its hydrolysis product with a compound having one α,β-unsaturated carbonyl group in the molecule in the presence of inorganic particles, preferably in the presence of an organic solvent or aqueous solvent containing inorganic particles, and coating the surface of the inorganic particles with the reaction product. This mixing may be performed by simply mixing and stirring at room temperature, but the coating proceeds faster when heated. It is preferable to perform the mixing at a temperature ranging from room temperature to 150° C. for 10 minutes to 20 hours. It is preferable to mix while dispersing, since the coating proceeds further. When performing the mixing while dispersing, a known dispersing machine can be used. Specific examples include a sand mill, a homogenizer, a ball mill, a paint shaker, and an ultrasonic dispersing machine. The coating also proceeds by hydrolyzing the alkoxy group of the reactant, but a certain amount of water is required for this hydrolysis reaction, and 0.5 to 1.5 equivalents (i.e., 0.5 equivalents or more and 1.5 equivalents or less) are added relative to the hydrolyzable group of the silicate. In addition, an acid or alkali may be added as a catalyst to promote the hydrolysis reaction. In this way, the surface-coated inorganic particles can be produced, and a dispersion in which the surface-coated inorganic particles are dispersed in an organic solvent can also be produced. As another method, a silicate compound having an amino group and / or its hydrolysis product and the compound having an α,β-unsaturated carbonyl group are mixed in advance in a solvent-free system to cause a partial reaction, and then the mixture is added to an organic solvent together with the inorganic particles to produce a dispersion in which the surface-coated inorganic particles are dispersed in an organic solvent.

[0027] As another method, the surface-coated inorganic particles can be prepared by mixing and reacting a silicate compound having an amino group and / or its hydrolysis product with a compound having one α,β-unsaturated carbonyl group in the molecule in the presence of inorganic particles, preferably in an organic solvent or aqueous solvent containing inorganic particles, to coat the surface of the inorganic particles with the reaction product. This mixing may be performed by simply mixing and stirring at room temperature as described above, but the reaction proceeds more quickly when heated. It is preferable to perform the mixing at a temperature ranging from room temperature to 150°C for 10 minutes to 20 hours. It is preferable to mix while dispersing, since the coating proceeds further. When performing the mixing while dispersing, a known dispersing machine can be used. Specific examples include a sand mill, a homogenizer, a ball mill, a paint shaker, and an ultrasonic dispersing machine. The coating also proceeds by hydrolyzing the alkoxy group of the reactant, but a certain amount of water is required for this hydrolysis reaction, and 0.5 to 1.5 equivalents (i.e., 0.5 equivalents or more and 1.5 equivalents or less) are added relative to the hydrolyzable group of the silicate. In order to promote the hydrolysis reaction, an acid or an alkali may be added as a catalyst. In this manner, the surface-coated inorganic particles can be produced, and a dispersion in which the surface-coated inorganic particles are dispersed in an organic solvent can also be produced.

[0028] In the present invention, the above-mentioned method can be used for production, but in order to produce surface-coated inorganic particles with a higher degree of precision, it is preferable to include the following first and second steps. (First step) This is a process in which inorganic particles are mixed with a silicate compound having an amino group and / or a hydrolysis product thereof in an aqueous solvent to coat the surfaces of the inorganic particles with the silicate compound having an amino group and / or a hydrolysis product thereof. (Second step) Next, the aqueous solvent is replaced with an organic solvent, and then a compound having one α,β-unsaturated carbonyl group in the molecule is mixed to coat the surfaces of the inorganic particles with the reaction product of the silicate compound having an amino group and / or its hydrolysis product, which has been coated on the surfaces of the inorganic particles, and the compound having an α,β-unsaturated carbonyl group.

[0029] First, in the first step, inorganic particles and a silicate compound having an amino group and / or a hydrolysis product thereof are mixed in an aqueous solvent, and the silicate compound having an amino group and / or a hydrolysis product thereof are adsorbed, precipitated, or reacted on the surface of the inorganic particles to coat the surface of the inorganic particles. If necessary, the pH may be adjusted or the silicate compound may be hydrolyzed. The aqueous solvent may contain water or an organic solvent that dissolves in water. When mixing inorganic particles and a silicate compound having an amino group and / or a hydrolysis product thereof in an aqueous solvent, it is preferable to prepare a dispersion in which the inorganic particles are suspended or dispersed using a normal suspending machine or dispersing machine. The inorganic particles may be suspended or dispersed in advance in an aqueous solvent using a normal suspending machine or dispersing machine, and the silicate compound having an amino group and / or a hydrolysis product thereof may be mixed into the aqueous dispersion. The content of the inorganic particles in the aqueous solvent can be appropriately set. This mixing may be performed by simply mixing and stirring at room temperature in the same manner as above, but the reaction proceeds more quickly when heat is applied. It is preferable to carry out the process at room temperature to reflux temperature for 10 minutes to 20 hours. It is preferable to mix while dispersing, since the coating will proceed further. When carrying out the process while dispersing, a known dispersing machine can be used. Specifically, a sand mill, a homogenizer, a ball mill, a paint shaker, an ultrasonic dispersing machine, etc. can be mentioned. The coating also proceeds by hydrolyzing the alkoxy group of the reactant, but a certain amount of water is required for this hydrolysis reaction, and 0.5 to 1.5 equivalents (i.e., 0.5 equivalents or more and 1.5 equivalents or less) are added relative to the hydrolyzable group of the silicate. In addition, an acid or an alkali may be added as a catalyst to promote the hydrolysis reaction. Note that both the suspension and the dispersion represent a state in which fine particles are dispersed in a liquid, but it is generally understood that fine particles are more likely to settle in the suspension than in the dispersion. However, for convenience, no particular distinction is made between the suspension and the dispersion in this specification, and the suspension is also called the dispersion.

[0030] Next, in the second step, the aqueous solvent is replaced with an organic solvent, and the inorganic particles are suspended or dispersed in the organic solvent. The replacement method can be a conventional method such as centrifugation, decantation, and flushing. A preferred method is to mix a surfactant and an organic solvent with the aqueous solvent containing inorganic particles coated with a silicate compound having an amino group and / or a hydrolysis product thereof, precipitate the inorganic particles, and, if necessary, perform solid-liquid separation, and then transfer the inorganic particles to the organic solvent. The surfactant is preferably an anionic surfactant, which becomes an anion when dissociated in water, and neutralizes the silicate compound having an amino group and / or a hydrolysis product thereof coated in the first step, thereby coagulating and precipitating the inorganic particles. The surfactant is preferably a monoalkyl sulfate (ROSO3 - M + ), alkyl polyoxyethylene sulfate (RO(CH2CH2O) m SO3 - M + ), alkylbenzene sulfonate (RCH2CHC6H4SO3 - M + ), monoalkyl phosphate (ROPO(OH)O - M +), but dialkyl sulfosuccinates such as sodium di(2-ethylhexyl) sulfosuccinate are preferred. The above R represents an alkyl chain having 12 to 15 carbon atoms (i.e., 12 to 15), m is an integer of 1 to 150 (i.e., 1 to 150), and M is at least one selected from alkali metals and alkaline earth metals. For solid-liquid separation, a conventionally known method can be used, and methods such as centrifugation, filtration, and ultrafiltration can be used to remove excess silicate compounds, surfactants, etc., and washing may be performed as necessary. Furthermore, after recovering the precipitated inorganic particles by solid-liquid separation, it is more preferred to heat treat (dry) them at a temperature of 80 to 200°C (i.e., 80°C to 200°C), because the silicate compound having an amino group and / or its hydrolysis product is more firmly coated on the surface of the inorganic particles. A more preferred temperature is 100 to 160°C (i.e., 100°C to 160°C). Next, the inorganic particles that have been separated from the solid-liquid mixture or the inorganic particles that have been heat-treated are suspended or dispersed in an organic solvent using a suspending machine or a dispersing machine to form a dispersion. The content of the inorganic particles can be appropriately set. As the organic solvent, the above-mentioned organic solvents can be appropriately used. It is preferable that the organic solvent does not contain water, and the water content is preferably 1 mass% or less.

[0031] Next, the inorganic particles coated with the silicate compound having an amino group and / or its hydrolysis product are dispersed in an organic solvent, and then a compound having one α,β-unsaturated carbonyl group in the molecule is mixed and reacted to coat the surfaces of the inorganic particles with the reaction product of the silicate compound having an amino group and / or its hydrolysis product and the compound having an α,β-unsaturated carbonyl group.

[0032] When a compound having one α,β-unsaturated carbonyl group in the molecule is mixed with an organic solvent dispersion of inorganic particles coated with the above-mentioned silicate compound having an amino group and / or its hydrolysis product, this compound reacts with the silicate compound having an amino group coated on the surface of the inorganic particles and / or its hydrolysis product, and the resulting reaction product coats the surface of the inorganic particles. The silicate compound having an amino group coated on the surface of the inorganic particles and / or its hydrolysis product combines with the α,β-unsaturated carbonyl compound to synthesize a silicate compound having an alkyl chain with a long carbon number on the surface of the inorganic particles. The compound having an α,β-unsaturated carbonyl group to be reacted is preferably a compound having one α,β-unsaturated carbonyl group in the molecule and further having an ether bond in the molecule, and as the compound having an ether bond, an ethylene glycol chain having a polymerization number n=2 to 10 (i.e., 2 or more and 10 or less), a propylene glycol chain having a polymerization number n=2 to 10 (i.e., 2 or more and 10 or less) or a compound having a 5- or 6-membered cyclic group is more preferable, and a (meth)acrylate or an alkoxy polyalkylene glycol (meth)acrylate having a 5- or 6-membered cyclic group (i.e., a 5- or 6-membered cyclic group) is even more preferable.

[0033] The compound having an α,β-unsaturated carbonyl group may be mixed and stirred at room temperature as described above, but the reaction proceeds faster when heated. It is preferable to perform the mixing at room temperature to reflux temperature for 10 minutes to 20 hours. It is preferable to mix while dispersing, since the coating proceeds further. When performing the mixing while dispersing, a known dispersing machine can be used. Specific examples include a sand mill, homogenizer, ball mill, paint shaker, ultrasonic dispersing machine, etc. In this way, the surface-coated inorganic particles can be produced, and a dispersion in which the surface-coated inorganic particles are dispersed in an organic solvent can also be produced. When the amino group of the silicate compound having an amino group and / or its hydrolysis product is a mole and the compound having an α,β-unsaturated carbonyl group is b mole, it is preferable that 0.8≦a / b≦10, more preferably 1≦a / b≦10, even more preferably 1≦a / b≦8, and most preferably 1≦a / b≦6.

[0034] In the present invention, in order to produce a higher quality organic solvent dispersion, it is preferable to include the following third and fourth steps. (Third step) This is a step in which a poor solvent is added to the organic solvent dispersion obtained in the second step, followed by solid-liquid separation to recover the surface-coated inorganic particles. (Fourth step) The next step is to disperse the recovered surface-coated inorganic particles in an organic solvent.

[0035] In the third step, a poor solvent is added to the organic solvent in which the surface-coated inorganic particles produced in the second step are suspended, and solid-liquid separation is performed to recover the surface-coated inorganic particles. The solid-liquid separation can be performed using a conventional method, and the surface-coated inorganic particles are recovered using a method such as centrifugation, filtration, or ultrafiltration. When a poor solvent is mixed with an organic solvent in which the surface-coated inorganic particles are dispersed, the surface-coated inorganic particles aggregate and precipitate, making solid-liquid separation easy. The poor solvent can be appropriately selected, and a polar solvent such as alcohol or a non-polar solvent such as hexane, benzene, or petroleum ether can be used. The amount of the poor solvent added can be appropriately set as long as the surface-coated inorganic particles aggregate. The aggregated surface-coated inorganic particles can be separated from the organic solvent and the poor solvent by solid-liquid separation, and excess compounds can be removed, and the particles may be washed and dried as necessary. The drying temperature can be appropriately set, and is preferably 80 to 200° C. (ie, 80° C. or higher and 200° C. or lower), and more preferably 100 to 160° C. (ie, 100° C. or higher and 160° C. or lower).

[0036] In the fourth step, the recovered surface-coated inorganic particles are mixed with an organic solvent and dispersed in the organic solvent. After the third step, the solid-liquid separated surface-coated inorganic particles (including inorganic particles dried after solid-liquid separation) are suspended or dispersed in an organic solvent to produce an organic solvent dispersion. The organic solvent may be one described above, and a known suspending or dispersing device may be used as the means for suspending or dispersing.

[0037] By mixing the surface-coated inorganic particles produced as described above with an organic solvent, an organic solvent dispersion can be produced. In addition, a coating composition can be produced by mixing the surface-coated inorganic particles with the organic solvent and a resin, or by mixing the organic solvent dispersion with a resin. A known suspending machine or dispersing machine can be used for mixing. Additives such as dispersants may be added appropriately to the organic solvent dispersion or coating composition. The organic solvent dispersion of the surface-coated inorganic particles produced in this way or the coating composition can be applied or sprayed onto a substrate to produce a surface-coated inorganic particle layer. The substrate is not particularly limited, and glass, plastic, ceramic, metal, etc. can be used. A layer of the surface-coated inorganic particles can be formed on the substrate and cured as necessary. Curing can be performed by a conventional method as appropriate, and drying at a temperature of 50 to 200 ° C (i.e., 50 ° C or more and 200 ° C or less) is preferable, and drying at a temperature of 80 to 150 ° C (i.e., 80 ° C or more and 150 ° C or less) is more preferable. The curing time can be set appropriately. In addition, the film thickness can be set appropriately. EXAMPLES

[0038] Examples and comparative examples are shown below, but the present invention is not limited to these examples.

[0039] Example 1 0.48g of 3-aminopropyltrimethoxysilane (KBM-903, Shin-Etsu Chemical Co., Ltd.), 29.76g of ion-exchanged water, and 0.16g of acetic acid were mixed together to obtain an aqueous solution, to which 1.6g of titanium oxide (TTO-51A, Ishihara Sangyo Kaisha, Ltd.) and 98g of 0.05mm zirconia beads were added and dispersed using a beads mill. After removing the beads, the mixture was centrifuged to collect the supernatant, and an aqueous dispersion of titanium oxide treated with 3-aminopropyltrimethoxysilane (TiO2 concentration 5%) was obtained.

[0040] Next, 3.76 g of dioctyl sodium sulfosuccinate (Sigma-Aldrich Japan, hereafter referred to as "DSS") dissolved in 40 g of toluene was added to 80 g of the obtained aqueous dispersion, and the mixture was left overnight and then solvent-substituted. A Dean-Stark apparatus was attached and the mixture was dehydrated and heated at an oil bath temperature of 140°C for 4 hours to obtain a toluene dispersion of titanium oxide treated with 3-aminopropyltrimethoxysilane (TiO2 concentration adjusted to 10%).

[0041] Next, 10 g of 1-methoxy-2-propanol, i.e., propylene glycol monomethyl ether (hereinafter referred to as "PGME") was added to 10 g of the obtained toluene dispersion, and then 0.183 g of methoxy-triethylene glycol acrylate (manufactured by Kyoeisha Chemical Co., Ltd.: Light Acrylate (registered trademark) MTG-A, hereinafter referred to as "MTG-A") and 0.339 g of triethylamine (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were added and stirred at 65 ° C. for 24 hours. After the stirring was completed, 40 g of petroleum ether (poor solvent) was added and the precipitate was collected by centrifugation. PGME was added to the precipitate and dispersed to obtain PGME dispersion 1.

[0042] Example 2 The same procedure as in Example 1 was carried out except that 0.183 g of methoxy-polyethylene glycol acrylate (manufactured by Kyoeisha Chemical Co., Ltd.: Light Acrylate (registered trademark) 130A, hereinafter referred to as "130A") was used instead of MTG-A, to obtain PGME Dispersion 2.

[0043] Example 3 The same procedure as in Example 1 was carried out except that the amount of MTG-A added was 0.061 g and N,N-dimethylacetamide (hereinafter referred to as "DMAc") was used instead of PGME, thereby obtaining DMAc dispersion 3.

[0044] Example 4 2 g of titanium oxide (Ishihara Sangyo Kaisha: TTO-51A) and 65 g of 0.1 mm zirconia beads were added to a solution obtained by mixing 0.225 g of KBM-903, 0.275 g of MTG-A, and 37.5 g of PGME, and the mixture was dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain PGME dispersion 4.

[0045] Example 5 0.235 g of KBM-903, 0.265 g of methoxydipropylene glycol acrylate (Kyoeisha Chemical Co., Ltd.: Light Acrylate (registered trademark) DPM-A), and 37.5 g of PGME were mixed to obtain a solution, to which 2 g of titanium oxide (Ishihara Sangyo Kaisha Co., Ltd.: TTO-51A) and 65 g of 0.1 mm zirconia beads were added and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain PGME Dispersion 5.

[0046] Example 6 2 g of titanium oxide (TTO-51A, manufactured by Ishihara Sangyo Kaisha) and 65 g of 0.1 mm zirconia beads were added to a solution obtained by mixing 0.135 g of KBM-903, 0.365 g of 130A, and 37.5 g of PGME, and the solution was dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain PGME dispersion 6.

[0047] Example 7 2 g of titanium oxide (Ishihara Sangyo Kaisha: TTO-51A) and 65 g of 0.1 mm zirconia beads were added to a solution obtained by mixing 0.213 g of KBM-903, 0.287 g of 130A, and 37.5 g of PGME, and the solution was dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain PGME Dispersion 7.

[0048] Example 8 2 g of titanium oxide (Ishihara Sangyo Kaisha: TTO-51A) and 65 g of 0.1 mm zirconia beads were added to a solution of 0.427 g of KBM-903, 0.173 g of MTG-A, and 37.4 g of DMAc, and the mixture was dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain DMAc dispersion 8.

[0049] Example 9 0.316 g of KBM-903, 0.284 g of 130A, and 37.4 g of DMAc were mixed to obtain a solution, to which 2 g of titanium oxide (TTO-51A manufactured by Ishihara Sangyo Kaisha, Ltd.) and 65 g of 0.1 mm zirconia beads were added and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain DMAc Dispersion 9.

[0050] Example 10 0.414 g of KBM-903, 0.186 g of 130A, and 37.4 g of DMAc were mixed to obtain a solution, to which 2 g of titanium oxide (TTO-51A manufactured by Ishihara Sangyo Kaisha, Ltd.) and 65 g of 0.1 mm zirconia beads were added and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain DMAc dispersion 10.

[0051] Example 11 0.316 g of KBM-903, 0.284 g of 130A, and 37.4 g of DMAc were mixed to obtain a solution, to which 2 g of zirconium oxide (UEP-100 manufactured by Daiichi Kigenso Kagaku Kogyo Co., Ltd.) and 65 g of 0.1 mm zirconia beads were added and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain DMAc dispersion 11.

[0052] Comparative Example 1 0.6 g of 3-aminopropyltrimethoxysilane (Kobm-903, Shin-Etsu Chemical Co., Ltd.) and 37.4 g of DMAc were mixed, and 2 g of titanium oxide (TTO-51A, Ishihara Sangyo Kaisha, Ltd.) and 65 g of 0.1 mm zirconia beads were added to the mixed solution, and the mixture was dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected, but all of the titanium oxide had precipitated.

[0053] [Reference example 1] The titanium oxide aqueous dispersion (TiO2 concentration: 5%) treated with 3-aminopropyltrimethoxysilane prepared in Example 1 was used as a reference sample for evaluating dispersibility.

[0054] In Examples 1 to 11 and Reference Example 1, the particle size distribution was measured.

[0055] [Particle size distribution measurement] A dynamic light scattering (DLS) particle size distribution measuring device (Microtrack-Bell: Nanotrac (registered trademark) Wave2 UZ152) was used to measure the particle size distribution of inorganic particles in the dispersion, and cumulative particle size distributions D10, D50, and D90 were measured. The results are shown in Table 1. As described above, a / b in Table 1 represents the molar ratio of amino groups and compounds having α,β-unsaturated carbonyl groups when the amino groups of the silicate compound having an amino group and / or its hydrolysis product in the reaction product are a mole, and the compounds having α,β-unsaturated carbonyl groups are b moles. In Examples 1 to 3, since "solvent replacement" is performed, there is a discrepancy between a / b obtained from the amount of silicate compound having an amino group and / or its hydrolysis product and the amount of compound having an α,β-unsaturated carbonyl group, and the actual a / b. Therefore, for a / b in Examples 1 to 3, the organic solvent dispersions obtained were subjected to thermogravimetric analysis, and the calculated values ​​were calculated from the mass loss, as shown in Table 1.

[0056] [Table 1]

[0057] In the dispersions of Examples 1 to 11, the D50 value of the particle size distribution was around 40 nm or less, which was not significantly different from the D50 of the aqueous dispersion of Reference Example 1. It was therefore found that the particles were sufficiently dispersed in organic solvents, similar to the aqueous dispersion of Reference Example 1.

[0058] Example 12 0.445 g of KBM-903, 1.225 g of 130A, and 21.92 g of PGME were mixed to obtain a solution, to which 8.4 g of titanium oxide (TTO-51N manufactured by Ishihara Sangyo Kaisha, Ltd.) and 65 g of 0.1 mm zirconia beads were added and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain PGME dispersion 12.

[0059] Example 13 8.4 g of titanium oxide (TTO-51N, manufactured by Ishihara Sangyo Kaisha) and 65 g of 0.1 mm zirconia beads were added to a solution obtained by mixing 0.716 g of KBM-903, 0.964 g of 130A, and 21.92 g of PGME, and the solution was dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain PGME dispersion 13.

[0060] Example 14 8.4 g of titanium oxide (TTO-51N, manufactured by Ishihara Sangyo Kaisha) and 65 g of 0.1 mm zirconia beads were added to a solution obtained by mixing 0.885 g of KBM-903, 0.795 g of 130A, and 21.92 g of PGME, and the solution was dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain PGME dispersion 14.

[0061] Example 15 1.092 g of KBM-903, 0.558 g of 130A, and 21.92 g of PGME were mixed to obtain a solution, to which 8.4 g of titanium oxide (TTO-51N manufactured by Ishihara Sangyo Kaisha, Ltd.) and 65 g of 0.1 mm zirconia beads were added and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain PGME dispersion 15.

[0062] Example 16 1.324 g of KBM-903, 0.356 g of 130A, and 21.92 g of PGME were mixed to obtain a solution, to which 8.4 g of titanium oxide (TTO-51N manufactured by Ishihara Sangyo Kaisha, Ltd.) and 65 g of 0.1 mm zirconia beads were added and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain PGME dispersion 16.

[0063] Example 17 1.079 g of KBM-903, 0.601 g of 130A, and 21.92 g of PGME were mixed, and then 8.4 g of titanium oxide (Ishihara Sangyo Kaisha, Ltd.: TTO-V5) and 65 g of 0.1 mm zirconia beads were added to the solution and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain PGME dispersion 17.

[0064] Example 18 0.885 g of KBM-903, 0.795 g of 130A, and 21.92 g of PGME were mixed, and then 8.4 g of titanium oxide (Ishihara Sangyo Kaisha, Ltd.: TTO-V5) and 65 g of 0.1 mm zirconia beads were added to the solution and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain PGME dispersion 18.

[0065] Example 19 1.092 g of KBM-903, 0.558 g of 130A, and 21.92 g of PGME were mixed, and then 8.4 g of titanium oxide (Ishihara Sangyo Kaisha, Ltd.: TTO-V5) and 65 g of 0.1 mm zirconia beads were added to the solution and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain PGME dispersion 19.

[0066] Example 20 0.789 g of KBM-903, 0.891 g of methoxydipropylene glycol acrylate (Kyoeisha Chemical Co., Ltd.: Light Acrylate (registered trademark) DPM-A, hereinafter referred to as "DPM-A"), and 21.92 g of PGME were mixed, and then 8.4 g of titanium oxide (Ishihara Sangyo Kaisha Co., Ltd.: TTO-V5) and 65 g of 0.1 mm zirconia beads were added to this solution and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain PGME dispersion 20.

[0067] Example 21 0.959 g of KBM-903, 0.721 g of DPM-A, and 21.92 g of PGME were mixed to obtain a solution, to which 8.4 g of titanium oxide (TTO-V5 manufactured by Ishihara Sangyo Kaisha, Ltd.) and 65 g of 0.1 mm zirconia beads were added and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain PGME dispersion 21.

[0068] Example 22 0.959 g of KBM-903, 0.721 g of DPM-A, and 21.92 g of PGME were mixed to obtain a solution, to which 8.4 g of titanium oxide (TTO-51N manufactured by Ishihara Sangyo Kaisha, Ltd.) and 65 g of 0.1 mm zirconia beads were added and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain PGME dispersion 22.

[0069] Example 23 1.221 g of KBM-903, 0.459 g of DPM-A, and 21.92 g of PGME were mixed to obtain a solution, to which 8.4 g of titanium oxide (TTO-V5 manufactured by Ishihara Sangyo Kaisha, Ltd.) and 65 g of 0.1 mm zirconia beads were added and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain PGME dispersion 23.

[0070] Example 24 1.063 g of KBM-903, 0.617 g of tetrahydrofurfuryl acrylate (Kyoeisha Chemical Co., Ltd.: Light Acrylate (registered trademark) THF-A, hereinafter referred to as "THF-A"), and 21.92 g of PGME were mixed to obtain a solution, to which 8.4 g of titanium oxide (Ishihara Sangyo Kaisha Co., Ltd.: TTO-V5) and 65 g of 0.1 mm zirconia beads were added and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain PGME dispersion 24.

[0071] Example 25 0.927 g of KBM-903, 0.753 g of MTG-A, and 21.92 g of PGME were mixed, and then 8.4 g of titanium oxide (Ishihara Sangyo Kaisha, Ltd.: TTO-V5) and 65 g of 0.1 mm zirconia beads were added to the solution and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain PGME dispersion 25.

[0072] Example 26 0.883 g of KBM-903, 0.797 g of DPM-A, and 21.92 g of PGMEA (propylene glycol monomethyl ether acetate) were mixed to obtain a solution, to which 8.4 g of titanium oxide (Ishihara Sangyo Kaisha, Ltd.: TTO-V5) and 65 g of 0.1 mm zirconia beads were added and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain PGMEA dispersion 26.

[0073] Example 27 0.959 g of KBM-903, 0.721 g of DPM-A, and 21.92 g of ethanol (EtOH) were mixed to obtain a solution, to which 8.4 g of titanium oxide (TTO-V5 manufactured by Ishihara Sangyo Kaisha, Ltd.) and 65 g of 0.1 mm zirconia beads were added and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain ethanol dispersion 27.

[0074] Example 28 0.959g of KBM-903, 0.721g of DPM-A, and 21.92g of isopropyl alcohol (IPA) were mixed to obtain a solution, to which 8.4g of titanium oxide (Ishihara Sangyo Kaisha: TTO-V5) and 65g of 0.1mm zirconia beads were added and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain isopropyl alcohol dispersion 28.

[0075] Example 29 0.883g of KBM-903, 0.797g of DPM-A, and 21.92g of methyl ethyl ketone (MEK) were mixed, and then 8.4g of titanium oxide (Ishihara Sangyo Kaisha, Ltd.: TTO-V5) and 65g of 0.1mm zirconia beads were added to the solution and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected to obtain methyl ethyl ketone dispersion 29.

[0076] Comparative Example 2 1.030g of KBM-903, 0.650g of 1,6-hexanediol diacrylate (Kyoeisha Chemical Co., Ltd.: Light Acrylate (registered trademark) 1,6HX-A), and 21.92g of PGM were mixed into a solution, to which 8.4g of titanium oxide (Ishihara Sangyo Kaisha Co., Ltd.: TTO-V5) and 65g of 0.1mm zirconia beads were added and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected, but all of the titanium oxide had precipitated.

[0077] Comparative Example 3 0.539g of KBM-903, 1.141g of PEG600# diacrylate (Kyoeisha Chemical Co., Ltd.: Light Acrylate (registered trademark) 14EG-A), and 21.92g of PGME were mixed to obtain a solution, to which 8.4g of titanium oxide (Ishihara Sangyo Kaisha Co., Ltd.: TTO-V5) and 65g of 0.1mm zirconia beads were added and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected, but all of the titanium oxide had precipitated.

[0078] Comparative Example 4 1.083g of KBM-903, 0.650g of trimethylolpropane triacrylate (Toagosei Co., Ltd.: Aronix (registered trademark) M-309), and 21.92g of PGME were mixed to obtain a solution, to which 8.4g of titanium oxide (Ishihara Sangyo Co., Ltd.: TTO-V5) and 65g of 0.1mm zirconia beads were added and dispersed using a beads mill. After removing the beads, the mixture was centrifuged and the supernatant was collected, but the entire amount of titanium oxide had precipitated.

[0079] The dispersion states in Examples 12 to 29 and Comparative Examples 2 to 4 are shown in Table 2. A good dispersion state is indicated by ◯, a dispersion state was observed but the solid content was below 5% or more in concentration, and a no dispersion state is indicated by ×. As the α,β-unsaturated carbonyl compound in Table 2, a mono-α,β-unsaturated carbonyl compound having one C=C bond in the molecule (i.e., a compound having one α,β-unsaturated carbonyl group in the molecule) was used in Examples 12 to 29, and other di- or tri-unsaturated carbonyl compounds having 2 to 3 C=C bonds in the molecule were used in Comparative Examples 2 to 4.

[0080] [Paint preparation 1] Each curable coating composition was prepared by mixing 4 g of each of the organic solvent dispersions containing titanium dioxide fine particles (TTO-51N) obtained in Examples 12 to 16 and Example 22, 0.25 g of dipentaerythritol hexaacrylate (M-405, manufactured by Toagosei Co., Ltd.), 0.25 g of urethane acrylate (M-1200, manufactured by Toagosei Co., Ltd.), 0.025 g of IRGACURE (registered trademark)-184, 0.4 g of diacetone alcohol, and 0.04 g of a leveling agent (KY-1203, manufactured by Shin-Etsu Chemical Co., Ltd.) so that the refractive index of the film was 1.8 to 1.82.

[0081] [Paint preparation 2] Each curable coating composition was prepared by mixing 4 g of each of the organic solvent dispersions containing titanium dioxide fine particles (TTO-V5) obtained in Examples 17 to 21, 23 to 29 and Comparative Examples 2 to 4, 0.21 g of dipentaerythritol hexaacrylate (M-405, manufactured by Toagosei Co., Ltd.), 0.21 g of urethane acrylate (M-1200, manufactured by Toagosei Co., Ltd.), 0.021 g of IRGACURE (registered trademark)-184, 0.4 g of diacetone alcohol, and 0.04 g of a leveling agent (KY-1203, manufactured by Shin-Etsu Chemical Co., Ltd.) so that the refractive index of the film was 1.8 to 1.82.

[0082] [Measurement of the refractive index of the coating, etc.] Each of the curable coating compositions prepared above was applied to a glass substrate as a coating liquid prepared as a paint, pre-dried at 150°C for 5 minutes, and then irradiated with a high-pressure mercury lamp to cure, forming three coatings with different thicknesses for each of the curable coating compositions. The haze of the resulting coating was measured with a haze meter (NDH-7000, manufactured by Nippon Denshoku Industries Co., Ltd.), and the thickness and refractive index of the coating at a measurement wavelength of 589 nm were measured with an ellipsometer (SmartSE, manufactured by Horiba, Ltd.). The film thickness and haze value were plotted, and the haze value at a film thickness of 3 μm was calculated by linear approximation, and is also shown in Table 2.

[0083] [Table 2]

[0084] [Reference example A] 0.827 g of 3-mercaptopropyltrimethoxysilane (K.S. Shin-Etsu Chemical Co., Ltd.: KBM-803, hereinafter referred to as "KBM-803"), 0.853 g of DPM-A, and 21.92 g of PGME were mixed to obtain a solution, to which 8.4 g of titanium oxide (K.S. Ishihara Sangyo Kaisha: TTO-V5) and 65 g of 0.1 mm zirconia beads were added, and the solution was dispersed using a beads mill. The molar ratio of KBM-803 to DPM-A was 1:1. After removing the beads, the solution was centrifuged, and the supernatant was collected to obtain PGME dispersion A. The dispersion state was measured in the same manner as above, and the state was △. The HAZE value of a film thickness of 3 μm was calculated to be 1.43.

[0085] [Reference example B] 0.827g of KBM-803, 0.853g of DPM-A, and 21.92g of PGMEA were mixed to obtain a solution, to which 8.4g of titanium oxide (TTO-V5 manufactured by Ishihara Sangyo Kaisha, Ltd.) and 65g of 0.1mm zirconia beads were added, and the solution was dispersed using a beads mill. The molar ratio of KBM-803 to DPM-A was 1:1. After removing the beads, the solution was centrifuged, and the supernatant was collected to obtain PGMEA dispersion B. The dispersion state was measured in the same manner as above, and the state was ◯. The HAZE value of a film thickness of 3 μm was calculated to be 1.19. [Industrial Applicability]

[0086] The present invention relates to surface-coated inorganic particles coated with a reaction product of a silicate compound having an amino group and / or its hydrolysis product with a compound having one α,β-unsaturated carbonyl group in the molecule, and the dispersibility of the inorganic particles in an organic solvent can be sufficiently improved, thereby enabling the inorganic particles to fully exhibit their functions and performance. In addition, the organic solvent dispersion and coating film of the obtained surface-coated inorganic particles can be excellent in transparency and refractive index.

Claims

1. Surface-coated inorganic particles, the surfaces of which are coated with a reaction product of a silicate compound having an amino group and / or its hydrolysis product with a compound having one α,β-unsaturated carbonyl group in the molecule.

2. 2. The surface-coated inorganic particles according to claim 1, wherein the compound having an α,β-unsaturated carbonyl group is a compound further having an ether bond.

3. 3. The surface-coated inorganic particle according to claim 1, wherein the compound having an α,β-unsaturated carbonyl group is a compound having an ethylene glycol chain (polymerization number n = 2 to 10), a propylene glycol chain (polymerization number n = 2 to 10), or a 5- or 6-membered cyclic group.

4. 4. The surface-coated inorganic particle according to claim 1, wherein the compound having an α,β-unsaturated carbonyl group is a (meth)acrylate having a 5- or 6-membered cyclic group or an alkoxypolyalkylene glycol (meth)acrylate.

5. 5. The surface-coated inorganic particles according to claim 1, wherein the compound having an α,β-unsaturated carbonyl group is tetrahydrofurfuryl acrylate, methoxytriethylene glycol acrylate, methoxypolyethylene glycol acrylate, or methoxydipropylene glycol acrylate.

6. 6. The surface-coated inorganic particle according to claim 1, wherein, when the amount of the amino group in the silicate compound having an amino group and / or the hydrolysis product thereof in the reaction product is a mole, and the amount of the compound having an α,β-unsaturated carbonyl group is b moles, the relationship a / b satisfies 0.8≦a / b≦10.

7. 7. The surface-coated inorganic particles according to claim 1, wherein the reactant is a low molecular weight silicate compound having 3 to 100 carbon atoms and / or a hydrolysis product thereof.

8. 8. The surface-coated inorganic particle according to claim 1, wherein the inorganic particle is composed of an inorganic core particle and an inorganic compound coated on the surface of the inorganic core particle.

9. 9. A surface-coated inorganic particle, wherein the inorganic particle according to claim 1 or the inorganic core particle according to claim 8 is a titanium oxide particle.

10. 10. An organic solvent dispersion of surface-coated inorganic particles, comprising the surface-coated inorganic particles according to claim 1 dispersed in an organic solvent.

11. A coating composition comprising the surface-coated inorganic particles according to any one of claims 1 to 9, an organic solvent, and a resin.

12. A coating composition comprising the organic solvent dispersion according to claim 10 and a resin.

13. a first step of mixing inorganic particles with a silicate compound having an amino group and / or a hydrolysis product thereof in an aqueous solvent to coat the surfaces of the inorganic particles with the silicate compound having an amino group and / or a hydrolysis product thereof; Next, a second step of replacing the aqueous solvent with an organic solvent, and then mixing a compound having one α,β-unsaturated carbonyl group in the molecule to coat the surfaces of the inorganic particles with a reaction product of the silicate compound having an amino group and / or its hydrolysis product and the compound having an α,β-unsaturated carbonyl group; A method for producing surface-coated inorganic particles comprising the steps of:

14. The method for producing surface-coated inorganic particles according to claim 13, wherein in the second step, a surfactant and an organic solvent are mixed into an aqueous solvent to transfer the inorganic particles to the organic solvent, thereby performing organic solvent replacement of the aqueous solvent, and then the compound having an α,β-unsaturated carbonyl group is mixed.

15. A method for producing surface-coated inorganic particles, comprising mixing inorganic particles, a silicate compound having an amino group and / or a hydrolysis product thereof, and a compound having one α,β-unsaturated carbonyl group in the molecule, and coating the surfaces of the inorganic particles with a reaction product of the silicate compound having an amino group and / or a hydrolysis product thereof and the compound having an α,β-unsaturated carbonyl group.

16. The method for producing surface-coated inorganic particles according to any one of claims 13 to 15, wherein, when the amount of the amino group in the silicate compound having an amino group and / or the hydrolysis product thereof is a mole and the amount of the compound having an α,β-unsaturated carbonyl group is b moles, a / b satisfies 0.8≦a / b≦10.

17. a third step of adding a poor solvent to the organic solvent dispersion obtained in the second step according to claim 13 or 14 to perform solid-liquid separation to recover surface-coated inorganic particles; Then, a fourth step of dispersing the recovered surface-coated inorganic particles in an organic solvent; A method for producing an organic solvent dispersion of surface-coated inorganic particles comprising the steps of:

18. A method for producing an organic solvent dispersion of surface-coated inorganic particles, comprising mixing inorganic particles, an amino group-containing silicate compound and / or a hydrolysis product thereof, and a compound having one α,β-unsaturated carbonyl group in the molecule in an organic solvent, coating the surfaces of the inorganic particles with a reaction product of the amino group-containing silicate compound and / or a hydrolysis product thereof and the compound having an α,β-unsaturated carbonyl group, and dispersing the reaction product in the organic solvent.

19. The method for producing an organic solvent dispersion according to claim 18, wherein a moles of the amino group in the silicate compound having an amino group and / or its hydrolysis product and b moles of the compound having an α,β-unsaturated carbonyl group satisfy 0.8≦a / b≦10.

20. A method for producing a surface-coated inorganic particle layer, comprising applying or spraying an organic solvent dispersion of the surface-coated inorganic particles according to claim 10 or a coating composition according to claim 11 or 12 onto a substrate.

Citation Information

Patent Citations

  • Polymerizable organic-inorganic composite particle

    JP2005220243A

  • Electronic endoscope

    JP2006068258A

  • Method for producing surface-treated inorganic filler

    JP2008031309A

  • Surface-treated inorganic powder

    JP2008174624A

  • Composite fine particle, method for producing the same and inkjet recording body using the same

    JP2009209025A